1998
DOI: 10.1016/s0896-6273(00)80593-0
|View full text |Cite
|
Sign up to set email alerts
|

A Common Network of Functional Areas for Attention and Eye Movements

Abstract: Functional magnetic resonance imaging (fMRI) and surface-based representations of brain activity were used to compare the functional anatomy of two tasks, one involving covert shifts of attention to peripheral visual stimuli, the other involving both attentional and saccadic shifts to the same stimuli. Overlapping regional networks in parietal, frontal, and temporal lobes were active in both tasks. This anatomical overlap is consistent with the hypothesis that attentional and oculomotor processes are tightly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

84
954
7
19

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,443 publications
(1,064 citation statements)
references
References 98 publications
84
954
7
19
Order By: Relevance
“…1998) (IC24) and left‐side‐dominant lateral prefrontal regions peaking at Brodmann's area (BA) 45 (IC18). The secondary analysis detected the posterior default mode network (DMN) (IC28), primary visual cortices (IC13), and executive control network (ECN, IC21) composed of the bilateral anterior dorsolateral and medial prefrontal cortices (MPF) (Duncan and Owen 2000; Smith et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1998) (IC24) and left‐side‐dominant lateral prefrontal regions peaking at Brodmann's area (BA) 45 (IC18). The secondary analysis detected the posterior default mode network (DMN) (IC28), primary visual cortices (IC13), and executive control network (ECN, IC21) composed of the bilateral anterior dorsolateral and medial prefrontal cortices (MPF) (Duncan and Owen 2000; Smith et al.…”
Section: Resultsmentioning
confidence: 99%
“…This area has been implicated in a wide variety of functions (Corbetta et al. 1998), including mental imagery (Mellet et al. 1996; Kosslyn and Thompson 2003; Ganis et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given that the parietal cortical areas mediating shifts of covert attention and eye movements overlap (Anderson et al, 1994;Corbetta et al, 1998) and that cognitive studies have also shown links between covert and overt attention (Hoffman, 1998;Klein, Kingstone, & Pontefract, 1992). Scinto et al found that individuals with AD were less accurate and slowed in shifting their gaze between a central fixation point and a target dot presented in sequence at peripheral locations.…”
Section: Attention Shiftingmentioning
confidence: 99%
“…Several more specific functions have been proposed for this region, including maintenance and manipulation of information in working memory (Goldman-Rakic, 1987;Owen et al, 1996), attentional control (Corbetta et al, 1998), choosing between alternative responses (Rowe et al, 2000), and representation and storage of the rules of a task (Miller et al, 2002;Derrfuss et al, 2004). The neuronal circuitry required to implement these functions is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%